2021
DOI: 10.1142/s0217732321500942
|View full text |Cite
|
Sign up to set email alerts
|

Background mode selection during asymptotic-de Sitter inflation

Abstract: For the first time, we choose non-flat vacuum mode for background spacetime based on the minimum number of created particles during early non-de Sitter inflation. In conventional methods for calculating the number of created particles, the flat background is selected automatically and causes a negative number problem for created particles during asymptotic-de Sitter inflation. In a covariant approach to curved spacetime, both real and background spacetimes should be selected, curved and consequently the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…• By adopting method (3), and using ( 12) and ( 33), the spectrum of particles created by purely geometric perturbations in Krein space can be expressed [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• By adopting method (3), and using ( 12) and ( 33), the spectrum of particles created by purely geometric perturbations in Krein space can be expressed [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, given that the theory of quantum fields in curved space plays a significant role in the discussion of inflation, so it can be expected that the result of considering the period of quasi-de Sitter inflation can affect the initial value of the quantum fluctuations of the scalar field in the early universe [11]. In fact, these effects can be reflected in the power spectrum of temperature fluctuations in cosmic background radiation [8,[12][13][14][15][16][17][18], which today, with the help of observational information sent to us by satellites, it has provided an important tool for judging the theories and models of cosmologists [9]. Reviewing of the published paper by using our proposal, it will be shown that the choice of non-flat background geometry will have an impact on the final results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation